Information Systems: Theory and Practice (Book). - Hendrickson, Harvey S.; Zieha, Eugene L. (The Accounting Review, 1985)
Reviews the book "Information Systems: Theory and Practice," by John G. Burch, Felix R. Strater and Gary Grudnitski.